How do you simplify {3( 2x - y - 2) - 2[ 3( x - 2y + 4) - 5( 2x - 3y + 2) \] \}?

2 Answers
Dec 25, 2017

10x-12y-28

Explanation:

  1. Distribute (Multiply them out)
    {3(2x-y-2)-2[3(x-2y+4)-5(2x-3y+2)]}
    {6x-3y-6-6x+6y-12-10x-15y-10}
  2. Add like terms and simplify.
    6x-6x+10x-3y+6y-15y-6-12-10
    10x-12y-28
Dec 25, 2017

20x-21y-10

Explanation:

Original: {3(2x-y-2)-2[3(x-2y+4)-5(2x-3y+2)]}

<=> {6x-3y-6-2[3x-6y+12-10x+15y-10]

<=> {6x-3y-6-6x+12y-24+20x-30y+20}

Now, we can rearrange

<=> {6x-6x+20x-3y-30y+12y-6-24+20}

= 20x-21y-10